Unusual branching in the palm Euterpe edulis Mart - Portela,Rita de Cássia Quitete (2009)
The unusual development of branches along the stem of Euterpe edulis is described for the first time. Branches originated at 2 to 190 cm from the ground. Ramified individuals and branches were able to produce reproductive structures and some branches produced roots. A plausible cause for the observed anomaly could be genetic problems due to small population sizes. The better agreement of this process can have a positive effect in the harvest of the heart of palm through the artificial induction of sprouts, what would prevent the death of the individual.